Homozygous mutation in ELMO2 may cause Ramon syndrome. Issue 3 (25th January 2018) - Mehawej, C.; Hoischen, A.; Farah, R.A.; Marey, I.; David, M.; Stora, S.; Lachlan, K.; Brunner, H.G.; Mégarbané, A.
Abstract : We report on a girl, born to first cousin Lebanese parents, with intellectual disability, seizures, repeated gingivorrhagia, enlarged lower and upper jaws, overgrowth of the gums, high arched and narrow palate, crowded teeth, hirsutism of the back, large abdomen and a small umbilical hernia. Cysts of the mandible, fibrous dysplasia of bones, and enlarged adenoids causing around 60% narrowing of the nasopharyngeal airways were noted at radiographic examination. Her brother presented with the same features in addition to a short stature, an ostium secundum, and more pronounced intellectual disability. He died at the age of 8 years from a severe pulmonary infection and repeated bleeding episodes. A clinical diagnosis of Ramon syndrome was made. Whole exome sequencing studies performed on the family revealed the presence of a novel homozygous missense mutation in ELMO2 gene, p.I606S in the affected individuals. Loss of function mutations in ELMO2 have been recently described in another clinically distinct condition: primary intraosseous vascular malformation or intraosseous hemangioma, called VMOS. Review of the literature and differential diagnoses are discussed. Abstract : Whole exome sequencing (WES) led to the identification of ELMO2 (c.1817T>G p.I606S) in a family with Ramon syndrome: (A) segregation of ELMO2 mutation (c.1817T>G p.I606S) with Ramon syndrome in the family, as confirmed by Sanger sequencing (B) conservation of the amino acid isoleucine at position 606 in ELMO2, among species.